Management and production of intangible cultural heritage - Lukić-Krstanović, Miroslava (Traditiones (Ljubljana), 2012)
The UNESCO Convention for the Safeguarding of the Intangible Cultural Heritage(ICH) has established new administrative rules and strategies of preservation, protection and implementation. The policy of intangible cultural heritage entails the conceptualization and configuration of the elements of intangible cultural heritage in the national framework as a model and as special perceptive strategies. Administrative stereotypes and pragmatism are confronted with scientific contextualization and with issues that determine various kinds of representation policies. In Serbia, intangible cultural heritage has been adopted as a strategy of state policy, accumulated scientific knowledge and various perceptions. Bearing in mind the specific social and political circumstances of the country in the periods of crisis and transition, the construct and status of intangible cultural heritage are manifested through ambivalent processes of worldwide networking and positioning through a symbolic fight of meanings as a "national issue".
Keywords: ethnology; Etnologija; intangible cultural heritage; Kulturna dediščina; cultural heritage; Nesnovna kulturna dediščina; UNESCO; Serbia; Srbija